2006
DOI: 10.1038/sj.ijo.0803258
|View full text |Cite
|
Sign up to set email alerts
|

Identification of women at risk of adverse weight development following pregnancy

Abstract: Background: It has been known for long time that pregnancy associated with weight problems women but few important factors have been identified, except for weight gain during pregnancy itself. Objective: To identify cutoffs for weight gain during pregnancy for identification of women at risk of high weight retention after pregnancy. Methods: A longitudinal analysis of 563 women who gave birth in 1984-1985 was used. Weight development during pregnancy was used as diagnostic test for high weight retention at 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…17,33 It is also very important to note that women who developed gestational diabetes have a 50% likelihood of developing type 2 diabetes within the following ten years.…”
Section: Long-term Complicationmentioning
confidence: 99%
“…17,33 It is also very important to note that women who developed gestational diabetes have a 50% likelihood of developing type 2 diabetes within the following ten years.…”
Section: Long-term Complicationmentioning
confidence: 99%
“…Furthermore, women that gain more weight during pregnancy are at increased risk for weight retention after pregnancy [17]. Environmental and lifestyle factors also have a significant impact on weight gain during the postpartum period [7,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Linne and Neovius have shown that women with weight gains of 16 kg or more during pregnancy were 2.5 times more likely to be a high weight retainer at 1-year postpartum. 30 Similarly, in the Norwegian Mother and Child cohort study, weight gain exceeding IOM guidelines resulted in a 42 kg weight retention at 18 months postpartum across all pregnancy BMI categories. 31 Excessive gestational weight gain has also been linked to the development of T2DM in a large prospective communitybased cohort study.…”
Section: The Interplay Of Weight Gain and Gdmmentioning
confidence: 96%